Dielectric Properties of Commercial non-Polar Polymers - Ahmed, Hameed M.; Aziz, Shuja-Aldeen B. (Sulaimani Journal for Pure and Applied Sciences, 2008)
Frequency and temperature dependence of dielectric constant (3') and dielectric loss (3''), in commercial non-polar polymers which were high density polyethylene (HDPE) and polystyrene (PS), of thicknesses 2.8 and 2.7mm respectively with diameter 5.6 cm, are studied in the temperature range (20- 110°С) and in the frequency range (1KHz-1MHz).It was observed that the dielectric constant of non-polar polymers decrease with increasing temperature as well as with frequency. The dielectric constant of PS increases with temperatures above 70°С, which is due to the glass transition temperature. It has been found that the dielectric loss of HDPE and PS decrease with increasing frequency and some loss peaks are observed. The dielectric loss of HDPE was found to be slightly temperature dependent, while the dielectric loss of PS, were found to increase slightly with increasing temperature.
Keywords: commercial nonpolar polymers; dielectric constant; dielectric loss; dielectric relaxation